2003
DOI: 10.1007/s00586-003-0528-9
|View full text |Cite
|
Sign up to set email alerts
|

The effects of pineal gland transplantation on the production of spinal deformity and serum melatonin level following pinealectomy in the chicken

Abstract: Pinealectomy frequently produces spinal deformity in some animal models, but the precise biological mechanism of this phenomenon remains obscure. The current study investigated the effects of an autograft pineal body on the development of spinal deformity and serum melatonin (MLT) concentration after pinealectomy in the chicken. Thirty-six chickens (2 days of age) were divided into three equal groups. While the removal of the pineal gland was performed in groups B and C, a pineal body autograft was surgically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 31 publications
0
27
0
1
Order By: Relevance
“…This group of work has demonstrated that pinealectomy produced scoliosis in chickens if the surgery was performed shortly after hatching. Pinealectomy resulted in a 100 % rate of deformity in all experiments if animals were rendered free of melatonin, the major product of the pineal gland [13,14]. Furthermore, these investigators demonstrated that development of scoliosis could be prevented by the replantation of the pineal gland in skeletal muscle or by the administration of melatonin as a replacement therapy [12], which however, could not be replicated by others [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…This group of work has demonstrated that pinealectomy produced scoliosis in chickens if the surgery was performed shortly after hatching. Pinealectomy resulted in a 100 % rate of deformity in all experiments if animals were rendered free of melatonin, the major product of the pineal gland [13,14]. Furthermore, these investigators demonstrated that development of scoliosis could be prevented by the replantation of the pineal gland in skeletal muscle or by the administration of melatonin as a replacement therapy [12], which however, could not be replicated by others [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Early reports were of an incidence of scoliosis after pinealectomy that was as high as 100% [14]. Subsequent investigations have found the incidence to be as low as 50% [5,6,18,21,22,24]. Factors proposed to account for this difference includes: the age at which the surgery is performed [10], the structures resected at pinealectomy [4], and the length of follow-up [13].…”
Section: Introductionmentioning
confidence: 99%
“…Pinealectomy generates spinal deformities due to the reduction in melatonin (Turgut et al 2003). The authors also observed a reduction in the number of chickens with scoliosis with an enhanced values of Cobb angle and rib-vertebra value in pineal-transplanted birds versus pinealectomized chicks.…”
Section: Bone Transplantationmentioning
confidence: 87%